Tauba Auerbach: Paula Cooper Gallery.("Projective Instrument" exhibition in New York) - Cburner, Rachel (Artforum international, 2016)
When considering Tau ba Auerbach's work of the past few years, lam often sent down a rabbit's hole of unfamiliar mathematical and scientific terms: entheogen, the Sierpinski curve, metamaterial, oscillator fret. I order books like The New Ambidextrous Universe and The Shape of Space and print out early-twentieth-century treatises like Projective Ornament. It is with great pleasure that I dive into her world, but also with a bit of trepidation: not only because — just between us — I don't really understand the fourth dimension, a theme that has fascinated Auerbach for several years now, but, more critically, because I worry that I may not be able to align her output with the subjects she so thoroughly researches to produce it.